Penanggulangan Bencana Berbasis Masyarakat Melalui Desa Siaga di Pagertoyo - Arfa, Heny Prasetyorini; Maulidta Karunianingtyas W (STIKes Ibnu Sina Ajibarang, 2025)
Geologically, Indonesia is an archipelagic country that is prone to natural disasters, this is due to Indonesia's geographical location which is surrounded by three earth plates, namely the Eurasian plate, the Indo-Australian plate, and the Pacific plate. As a result of the meeting of the three global plates, Indonesia is located on the path of the fire mountains or what is known as the Ring of Fire which makes Indonesia prone to natural disasters in the form of volcanic eruptions, natural disasters, earthquakes, tsunamis, landslides, floods, droughts, and others. Every region is vulnerable to natural disasters, both those directly influenced by nature and those influenced by humans. Natural disasters can have negative impacts in the form of economic losses, building damage, and loss of life. One effort to anticipate the negative impacts of natural disasters is through disaster mitigation. The purpose of this PKM Activity is to Teach the Community about Community-Based Disaster Management Through the Alert Village in Pagertoyo. Because emergencies can happen anytime and anywhere without exception, the method of implementing the activity consists of the preparation stage by providing socialization, implementation by providing training, assistance and evaluation. The results of the activity showed that most participants understood the material on Community-Based Disaster Management Through the Alert Village. The community is able to demonstrate disaster simulations for evacuating disaster victims and is able to demonstrate resuscitation on victims with respiratory arrest. With this PKM, it is hoped that the community will be able to carry out disaster mitigation to help disaster victims by evacuating victims and can help provide assistance to victims who have experienced respiratory arrest.